How can Industry 4.0 technologies and circular economy help companies and researchers collaborate and accelerate the transition to strong sustainability? A bibliometric review and a systematic literature review - de Oliveira Neto, G. C.; da Conceição Silva, A.; Filho, M. G. (International journal of environmental science and technology (Tehran), 2023)
The study aimed to evaluate the adoption of Industry 4.0 technologies in conjunction with eco-efficiency tools and circular economy that generate economic, environmental, and/or social gains, in addition to helping companies and researchers collaborate and accelerate the transition to strong sustainability. The methodology used in this study was the bibliometric review in order to assess the number of publications, countries surveyed, journals, research methods, sectors, and systematic literature review to analyze how the use of Industry 4.0 technologies and circular economy can help companies and researchers collaborate and accelerate the transition to strong sustainability. The study indicated eleven propositions based on Industry 4.0 technologies, eco-efficiency tools, and circular economy that help managers and researchers promote strong sustainability. The theoretical implications of the study consist of: cleaner production, which was the most used tool in conjunction with Industry 4.0 technologies in order to enhance the circular economy; simulation and Internet of things, which are more appropriate for the design of environment and eco-design; Internet of things, which enabled the structure of reverse logistics and big data; and cloud computing, which generated a system for selecting suppliers in the green supply chain. The practical implication of the study consists of suggesting insights on how the Industry 4.0 technologies could promote productivity and at the same time boost sustainability, mainly because some business managers have incipient knowledge about this subject. This is the first study to indicate how Industry 4.0 technologies and circular economy can help companies and researchers promote strong sustainability, denoting its originality/value. However, this study is exploratory, which is a limitation of this research.